Implementasi Webgis Untuk Penyebaran Apotek Dikota Rantau Prapat - Rapika Sari; Ibnu Rasyid Munthe; Rahmadani Pane (Jurnal Sistem Informasi, Teknik Informatika dan Teknologi Pendidikan, 2021)
Difficulties in finding the location of a pharmacy in a certain area resulted in the community's needs not being met. The purpose of this study is to implement a web-based geographic information system (Webgis) regarding the distribution of a number of pharmacies in Rantauprapat City. The benefits of Webgis can make it easier for the public to find out and find any point in pharmacies in Rantauprapat City by realizing a Geographic Information System. This study uses SDLC (System Development Life Cyle) design as a mechanism in designing Webgis Pharmacies, and uses UML (Unified Modeling Language) modeling as a geographic information system design model that helps simplify problems that can meet needs in modeling, building and describing communication. about a system using diagrams and supporting texts. It is hoped that this application can make it easier to find the needed pharmacy.